Sjögren sendromuna bağlı kuru göz hastalığında topikal %0.1 siklosporin A tedavisinin etkinliği - (:unkn) unknown (My University, 2003)
Amaç: Sjögren sendromlu (SS) kuru göz hastalarında topikal %0.1 siklosporin A (CsA) tedavisinin etkinliğini değerlendirmek. Gereç ve Yöntem: Çalışmaya 25 primer veya sekonder SS'lu kuru göz hastası dahil edildi. Hastaların bir gözlerine suni gözyaşı içinde hazırlanmış %0.1 CsA damlası, diğer gözlerine ise taşıyıcı olarak kullanılan suni gözyaşı damlası ile tedaviye başlandı. Tedavi öncesinde ve tedavinin L, 3. ve 6. ayında hastaların kuru göz bulguları Schirmer I testi, anestezili Schirmer testi, gözyaşı kırılma zamanı (GKZ), flouresein ve rose bengal ile oküler yüzey boyanma skorları ile değerlendirildi. Bulgular: CsA tedavisi alan gözlerde, tedavinin 3. ve 6. ayında Schirmer I testi (sırasıyla, p=0.03 ve p=0.008), anestezili Schirmer testi (sırasıyla, p=0.01 ve p=0.001), GKZ (sırasıyla, p=0.04 ve p=0.001), flouresein ile korneal boyanma (sırasıyla, p=0.03 and p=0.008) ve rose bengal skorlarında (sırasıyla, p=0.045 ve p=0.005) suni gözyaşı alan gözlere göre daha fazla dü-zelme olduğu saptandı. Tedavinin 3.ve 6.ayında, CsA tedavisi alan gözlerde Schirmer I testi, anestezili Schirmer testi ve GKZ'ında tedavi öncesine göre anlamlı artış saptandı (p<0.0001). Ayrıca, flouresein ile korneal boyanma skorunda 3.ve 6.ayda (sırasıyla, p=0.008 ve p<0.0001, rose bengal skorunda ise 6. ayda (p<0.0001) istatistiksel olarak anlamlı azalma olduğu görüldü. Suni gözyaşı tedavisi alan kontrol gözlerde ise yanlızca 6.ayda GKZ (p=0.001) ve flouresein skorunda (p=0.004) istatistiksel olarak anlamlı düzelme vardı. Sonuç: Topikal %0.1 CsA tedavisinin SS'lu hasta grubunda kuru göz bulgularında iyileşme sağladığı ve etkili bir tedavi seçeneği olabileceği sonucuna varıldı.

Purpose: To evaluate the efficacy of topical 0.1% cyclosporine A (CsA) aqueous solution in the treatment of dry eye disease in Sjögren syndrome (SS) patients. Methods: Twenty-five patients diagnosed as primary or secondary SS with dry eye disease were enrolled to this study. The patients used 0.1% CsA prepared in artificial tears in one eye and the other eye received artificial tears (vehicle) only. Lacrimal function tests including Schirmer I test, Schirmer test with anesthesia, tear break-up time and flourescein, and rose bengal staining of the ocular surface were recorded at baseline and 1,3, and 6 months after the initiation of treatment. Results: At 3 and 6 months, treatment with CsA gave significantly greater improvement than artificial tears (vehicle) in Schirmer I test (p=0.03 and p=0.008, respectively), Schirmer test with anesthesia (p=0.01 and p=0.001, respectively), tear breakup-time (p=0.04 and p=0.001, respectively), flourescein (p=0.03 and p-0.008, respectively) and rose bengal staining scores (p=0.045 and p=0.005, respectively) of ocular surface. Schirmer I test, Schirmer test with anesthesia, and tear break-up time increased significantly at 3 months and 6 months compared with the baseline scores in eyes treated with CsA (p<0.0001). Also, statistically significant imp-rovement from baseline score was observed at 3 months and 6 months in corneal flourescein staining scores (p=0.008 and p<0.0001, respectively) and at 6 months in rose bengal staining scores (p<0.0001). Significant improvement from baseline scores was observed only in tear bre-ak-up time (p=0.001) and corneal flourescein staining scores (p=0.004) at month 6 in the cont-rol eyes receiving artificial tears. Conclusion: We conclude, that topical 0.1% CsA treatment was effective in improving clinical signs of dry eye in this group of patients with SS.
The efficacy of topical 0.1% cyclosporine A in the treatment of dry eye disease associated with Sjögren syndrome
Keywords: Dermatoloji